Genetic evolution and molecular characteristics of avian influenza viruses in Jining from 2018 to 2023 - Zhao, Mingsheng; Dou, Huixin; Jiang, Yajuan; Jia, Yongjian; Yue, Ying; Li, Libo; Huang, Shiqing; Si, Meidi; Wang, Jingjing; Jiao, Boyan; Wang, Xiaoyu (Frontiers in Microbiology, 2025)
ObjectiveThis study aimed to analyze the genetic evolution and molecular characteristics of H5, H7, and H9 subtypes of avian influenza viruses in the external environment of poultry in Jining from 2018 to 2023, providing scientific evidence for the prevention and control of avian influenza.MethodsPositive samples of H5, H7, and H9 subtypes, collected from the poultry external environment in Jining between 2018 and 2023, were subjected to real-time quantitative PCR. Samples with cycle threshold (CT) values below 30 were selected for influenza virus capture and whole-genome sequencing. Phylogenetic analysis was conducted using bioinformatics software to construct an evolutionary tree, and amino acid mutation sites in the avian influenza virus sequences were analyzed.ResultsWhole-genome sequencing was completed for seven H5N1 strains, four H5N6 strains, one H7N9 strain, and 30 H9N2 strains. Homology analysis revealed that the nucleotide and amino acid sequences of the H5N1 subtype exhibited lower homology with those of the H5N6, H7N9, and H9N2 subtypes, indicating a greater genetic distance. Phylogenetic and molecular characteristic analyses showed that the seven H5N1 strains, four H5N6 strains, and one H7N9 strain were highly pathogenic, while all 30 H9N2 strains were low pathogenic. No mutations were identified at most receptor-binding sites, such as Q226L and G228S, in the H5N1, H5N6, and H7N9 strains, indicating limited mutation at these sites. However, some mutations were observed, suggesting that the virus retained some binding affinity for the human receptor α-2,6Gal. In contrast, mutations at receptor-binding sites, including G186V, A190T, and Q226L, were found in most of the H9N2 strains, increasing their likelihood of binding to α-2,6Gal and indicating a higher potential for human infection.ConclusionThe H5, H7, and H9 subtypes of avian influenza viruses are undergoing continuous dynamic evolution and exhibit significant genetic diversity. Enhanced monitoring of viral molecular evolution and research into cross-host transmission are essential.